2005
DOI: 10.1017/s002211200400309x
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady bubble propagation in a flexible channel: predictions of a viscous stick-slip instability

Abstract: We investigate the unsteady motion of a long bubble advancing under either prescribed pressure p b or prescribed volume flux q b into a fluid-filled flexible-walled channel at zero Reynolds number, an idealized model for the reopening of a liquidlined lung airway. The channel walls are held under longitudinal tension and are supported by external springs; the bubble moves with speed U. Provided p b exceeds a critical pressure p crit , the system exhibits two types of steady motion. At low speeds, the bubble ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 30 publications
(64 reference statements)
4
47
0
Order By: Relevance
“…Considering that the length of a single cell (Ϸ40 m) is greater than that of the capillary wave, the maximum pressure drop and shear stress change within a cell can be estimated to be the largest change in the magnitude of the wall pressure and shear stress in the capillary wave region, which are 6,454.9 dynes/cm 2 and 97.58 dynes/cm 2 , respectively. It should be noted, however, that these values may change because of the factors that have not been taken into account in our study, such as pulmonary surfactant (42,43,44,56,57), airway compliance (35)(36)(37), and non-planar topography of the airway wall resulting from the protrusion of airway epithelial cells (38).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering that the length of a single cell (Ϸ40 m) is greater than that of the capillary wave, the maximum pressure drop and shear stress change within a cell can be estimated to be the largest change in the magnitude of the wall pressure and shear stress in the capillary wave region, which are 6,454.9 dynes/cm 2 and 97.58 dynes/cm 2 , respectively. It should be noted, however, that these values may change because of the factors that have not been taken into account in our study, such as pulmonary surfactant (42,43,44,56,57), airway compliance (35)(36)(37), and non-planar topography of the airway wall resulting from the protrusion of airway epithelial cells (38).…”
Section: Resultsmentioning
confidence: 91%
“…In addition, transient pressure waves generated by plug rupture are believed to produce abnormal breath sounds known as respiratory crackles that are routinely used as an indicator of a wide range of respiratory disorders in clinics (30)(31)(32)(33). Although clinically considered more as a symptom of respiratory diseases than as a cause, several theoretical investigations have suggested that the progression of liquid plugs or air bubbles during airway reopening can potentially generate deleterious fluid mechanical stresses characterized by large wall shear and normal stresses (34)(35)(36)(37)(38)(39). There have also been experimental studies based on excised lungs or in vivo animal models that corroborate the theoretical predictions and demonstrate severe tissue damage in surfactantdeficient lungs as a result of repetitive airway reopening (40,41).…”
mentioning
confidence: 99%
“…Theory (23) predicts that the left-hand steady "pushing" solutions are unstable (at sufficiently long times) and therefore unrealizable experimentally when either the bubble pressure or the bubble volume flux is prescribed, although slow unsteady pushing may be an accessible mode of reopening transiently, particularly at low bubble pressures. Under low fixed volume flux, an oscillatory instability is predicted to develop at large times (23) for which the tube switches abruptly between slow pushing motion (when the bubble enlarges predominantly by transverse inflation without advancing appreciably) and rapid peeling motion (when the bubble enlarges by elongating rapidly while also shrinking in width); the longer the bubble, the greater the propensity to exhibit this unsteady oscillatory behavior. In conjunction with unpredictable avalanche effects operating throughout the airway network (2), such an instability would make airway recruitment under external ventilation difficult to control in the sense that imposing a steady volume flux can lead to strongly timedependent motion.…”
Section: Discussionmentioning
confidence: 99%
“…This low pressure provides the adhesive force that holds the tube walls together; the associated pressure gradient drives viscous flows within the tube.) For a bubble advancing with P b prescribed, provided Pb Ͼ Pbcrit, the peeling solution has been shown to be stable to time-dependent disturbances both theoretically (23,44) and experimentally (16,47,48); steady pushing motion, in contrast, is unstable to perturbations at long times if either the bubble pressure or the bubble volume flux is prescribed (23) and is therefore not accessible experimentally, although unsteady pushing motion may occur transiently at low Pb and low U. In summary, with pb prescribed, steady reopening is predicted to occur only for sufficiently large pb and it occurs preferentially at high bubble speeds in peeling mode; unsteady pushing motion may occur at low pressures and speeds (23), but this falls outside the framework of the present (steady) model.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation